Analysis of the Principles of Cooperation: Realization and Violation of the Maxim of Quantity in the "Lapor Pak!" - Husnul Hotimah (Research in Education, Technology, and Multiculture, 2023)
Abstract: The maxim of quantity is an utterance that contains brief information or is not excessive. This study aims to reveal and describe the realization and violation of the quantity maxims in the cooperative principle of the actors in the "Report Pak!" on Trans7. This study uses a qualitative method that will describe the results of the analysis of the maxims of quantity performed by the performers in the “Report Sir!” program. The quantitative method will produce descriptive data, namely in the form of words or sentences that clearly describe the results of the research that has been done. The data in this study are conversation fragments that obey and violate the maxim of quantity in the principle of cooperation. The data source for this research is the YouTube video “Report Sir!” which aired on Wednesday, April 4, 2023. The video has a duration of 09.49 minutes with the title "Kang Maman Investigates Pasukin, Instead Thinks Wendi's Twin!". The listening and note-taking technique was chosen as the data collection technique in this study. Based on the results of the research that has been done, in the program "Report Sir!", it can be seen that there are two conversations which are the realization of the maxim of quantity and four conversations which are violations of the maxim of quantity.   Keywords: The principle of cooperation, maxim of quantity, realization, violation, conversation.